Reflective Practice: Co-Creating Reflective Activities for Pharmacy Students - Kalbie Hokanson; Rene R. Breault; Cherie Lucas; Theresa L. Charrois; Theresa J. Schindel (Pharmacy, 2022)
Reflective practice is important in pharmacy education to support skill development for decision-making, critical thinking, problem-solving, and in continuing professional development and beyond. Despite the importance of reflective practice in higher education and professional practice, reflection assignments are not universally embraced by students. This project was initiated due to recent interest in the co-creation of pharmacy curriculum by students and faculty. The purpose of this project was to develop reflection assignments for pharmacy students. The principles of the analysis, design, development, implementation, evaluation (ADDIE) instructional design framework guided the development of reflection assignment templates for three focus areas: personal development, professional development, and professional identity formation. Templates included background and definitions for these specific focus areas as well as objectives, instructions, guiding questions, assessment methods, and submission requirements. A previously tested assessment rubric was adopted for reflection assignments. Development involved target audience and expert reviews and a trial implementation was held in a year 3 patient care skills course. The co-creation process enriched the experiences of students and faculty involved in it. Future co-creation projects including groups of students, formal evaluation of outcomes, and impact on the program will further support integration of reflective practice in the pharmacy curriculum.